A method for the estimation of overpressure generated by open air hydrogen explosions. (March 2018) - Mukhim, Euginia Diana; Abbasi, Tasneem; Tauseef, S.M.; Abbasi, S.A.
Abstract: The existing methods for calculating overpressure resulting from a vapour cloud explosion (VCE) were tested for their ability to predict overpressures from unconfined hydrogen explosions. For it, data collated from five reported experimental investigations on open air hydrogen explosions covering 1.4–300 m 3 volume of hydrogen-air mixtures and concentrations ranging 20–57% were employed. It was found that the existing VCE models are grossly inadequate for predicting the overpressure generated by unconfined hydrogen explosions. A new method was then developed for assessing overpressures from hydrogen explosions for a given concentration and volume of release based on Sach's scaling laws. The new model has much greater ability to fit the experimental data, hence much stronger ability to forecast the severity and consequences of hydrogen-based VCEs compared to the existing models. Highlights: A vapour cloud explosion (VCE) is a major risk associated with hydrogen use. Current methods for overpressure estimation from VCEs are inadequate for hydrogen. A new method of estimation of overpressures from hydrogen VCEs has been developed. It is based on data from hydrogen VCE tests of 1.4–300 m 3, 20–57% strength. 4 statistical tests show the new method is significantly better than the others.